2017
DOI: 10.21873/invivo.11073
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Between Expression of the Cancer/Testis Antigen KK-LC-1 and Helicobacter pylori Infection in Gastric Cancer

Abstract: Abstract. Background/Aim: Our previous study indicatedthat Kita-kyushu

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 13 publications
2
14
0
Order By: Relevance
“…In an earlier study, we reported that Hp infection induces expression of speci c CTAs, in addition to causing malignant transformation of host cells. Additionally, we found that, in clinical GC, there is a correlation between KK-LC-1 expression and Hp infection [13], [14]. These ndings suggest a possible correlation between KK-LC-1 expression and Hp infection, an early cancer-causing event.…”
Section: Read Full License Introductionsupporting
confidence: 55%
See 1 more Smart Citation
“…In an earlier study, we reported that Hp infection induces expression of speci c CTAs, in addition to causing malignant transformation of host cells. Additionally, we found that, in clinical GC, there is a correlation between KK-LC-1 expression and Hp infection [13], [14]. These ndings suggest a possible correlation between KK-LC-1 expression and Hp infection, an early cancer-causing event.…”
Section: Read Full License Introductionsupporting
confidence: 55%
“…Furthermore, in an earlier study, Fukuyama et al clari ed the speci c phenomena at the basis of the correlation between KK-LC-1 expression and Hp infection. Additionally, we previously showed how KK-LC-1 expression was frequently detected at non-tumour sites of the stomach occurring GC [14,16]. However, from these studies, it remained unclear whether KK-LC-1 was expressed in the stomach of patients who were not carrying a tumour and with Hp infection.…”
Section: Discussionmentioning
confidence: 99%
“…KK-LC-1 is expressed in 40% of non-small-cell lung cancer tissues, 4 81.6% of gastric cancer 5 and 75% of triple-negative breast cancer. Correlated with Helicobacter pylori infection, 7 KK-LC-1 can be frequently detected even in early stage of gastric cancer 8 and at the pre-cancerous condition of the stomach. Correlated with Helicobacter pylori infection, 7 KK-LC-1 can be frequently detected even in early stage of gastric cancer 8 and at the pre-cancerous condition of the stomach.…”
Section: Introductionmentioning
confidence: 99%
“…The titer was significantly higher in the group with expression of KK-LC-1 than in those without the expression. There was no difference observed between the groups with and without CTA ( Table 1) [16], which implied that HP infection induces the expression of the specific CTA, KK-LC-1, with tumorigenesis. In addition, the discrepancy in the effect of HP between mouse Mage-A3 induction in vitro and human MAGE-A3 of clinical gastric cancer was attributed to the fact that homology between human and mouse MAGE-A3/Mage-A3 is 42% [19] and that HP directly induces mouse Mage-A3 expression.…”
Section: Expression Of Ctas In Clinical Gastric Cancer Tumor With Hp mentioning
confidence: 90%
“…The expression rate of the CTAs-encoding gene is commonly less than 40% (Table 1) [12][13][14][15][16], except for the specific CTA in the specific tissue cancer such as 80% expression of MAGE-A1 in hepatic cell carcinoma [17]. Although the expression rate of Kitakyushu lung cancer antigen-1 (KK-LC-1) was typical in other tissue cancers (Table 2), it was highest among the CTAs in gastric cancer [18], implying that KK-LC-1 would be induced by specific tumorigenic factors, such as HP, in the stomach.…”
Section: Expression Of Ctas In Clinical Cancer Tumormentioning
confidence: 99%